Role of Ethical Culture in Creating Public Value - Sami, Abdul; Jusoh, Ahmad; Mahfar, Mastura; Qureshi, Muhammad Imran; Khan, Muhammad Muddassar (International Review of Management and Marketing, 2016)
The concept of public value is very important for public sector organization and it is considered that there is no more important topic in public administration and public policy than public value. The underlying principle of the pubic value concept is that the value to citizens should guide the operations of public organizations on the delivery of public services. The goal of all sectors of the economy, public and private, is to create or increase the value created by their contribution. The term ‘public value' can be defined as what the public values – what they are willing to make sacrifices of money and freedom to achieve, and describes the contribution made by the public sector to economic, social and environmental well-being of a society or nation. The concept of public value has been extended in many different ways but the major focus is on the sources of public value and how to create public value. In this study our main goal is to find the relationship between ethical culture and public value and what is the impact of ethical culture on public value. Ethical culture refers to the ethical quality of a work environment, which is defined as the shared values, norms, and beliefs that can stimulate ethical behavior. Organization's ethical culture is related to its employees' intended responses to observed and ultimately promotes ethical behavior and this ethical behavior is the backbone of public value creation. Keywords: Public Value, Ethical Culture, Public Organization, JEL Classifications: J10, M10